«Մահմեդական շարժումը» ռուսական առաջին բուրժուադեմոկրատական հեղափոխության տարիներին - Սաթենիկ Ավոյան (ՀՀ ԳԱԱ հրատ.)
Закавказские мусульмане, в их числе и татары, в основном не участвовали в революционных событиях, сохраняя верность самодержавию. Но при всем при этом их прогрессивная интеллигенция обратилась к правительству с петицией о предоставлении мусульманам и христианам равных прав. The first Russian bourgeois-democratic revolution awakened all the peoples of the empire and the Transcaucasian Tatars among them. These Transcaucasian Tatars, on the whole, did not participate in the global events of the revolution remaining faithful to the governing authorities.
Keywords: Modern History; Political Science